The development and validation of multidimensional workplace compassion scale: Linking its conceptualization and measurement - Mandliya, Anshul; Pandey, Jatin (Frontiers in Psychology, 2023)
Organizational compassion is a powerful force that possesses the capability to move individuals and groups towards a common good. Research on organizational compassion or compassion in the workplace has discussed its potential to reduce individual suffering and enhance positive emotions, wellbeing, and dignity. The existing literature lacks a valid and reliable measure of workplace compassion that follows the recent conceptualization of organizational compassion. This research presents the development and validation of workplace compassion scale. The scale development process consisted of four studies with a total sample of 947 respondents. In study 1, we developed the items for the new measure by considering the four-factor conceptualization of organizational compassion. Study 2 and 3 focuses on item purification and testing the model fit indices of the proposed scale. In study 4, we followed a time separated design to test the nomological network and discriminant validity of the workplace compassion scale. The final workplace compassion scale consists of 12 items that measure other-oriented / expressed compassion in the workplace. The scale is beneficial for providing impetus to future quantitative research in organizational compassion.